Some Properties of High Strength Sustainable Concrete Containing Glass Powder Waste - Wasan I. Khalil; Nazar F. Al-Obeidy (Diyala Journal of Engineering Sciences, 2018)
This investigation includes the use of glass wastes after recycling to produce high strength sustainable concrete. The glass waste used is prepared to be a natural Pozzolan class (N) according to ASTM C618 with fineness of about 7340 cm2/gm. Many concrete mixes with different percentages of glass waste powder as a partial replacement by weight of cement (10%, 15%, 20%, 25%, and 30%) were prepared to study some properties of concrete (compressive strength, splitting tensile strength, flexural strength, and modulus of elasticity at 60 day age). The test results indicate that the mechanical properties of concrete are improved with the increase of glass waste powder up to 15%, and then decreased. The maximum percentages of increase for compressive, splitting tensile, flexural strengths, and modulus of elasticity are 13.29%, 36.27%, 34.68%, and 8.2% respectively relative to the reference for concrete specimens containing 15% glass waste powder as a replacement by weight of cement.Corrosion inhibition of low carbon steel, stainless steel types 316 and 304 in hydrochloric acid by potassium iodide was investigated at different temperatures using weight loss and polarization electrochemical techniques